Radiological protection. X and gamma reference radiation for calibrating dosemeters and doserate meters and for determining their response as a function of photon energy. Dosimetry for radiation protection over the energy ranges from 8 keV to 1, 3 MeV and 4 MeV to 9 MeV Part 2, (22nd August 2019) - British Standards Institution,
No abstract available